CLINICAL CHARACTERISTICS AND PREVALENCE OF COMORBID PSYCHIATRIC DISORDERS IN CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER AT THE DEPARTMENT OF PSYCHIATRY, NATIONAL HOSPITAL OF PEDIATRICS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical characteristics of ADHD in children aged 6 – 12 years treated as outpatients at the Department of Psychiatry, National Children’s Hospital in 2024 – 2025.Subjects and Methods: A cross-sectional descriptive study was conducted on 110 children who were newly diagnosed with ADHD according to DSM-5 criteria at the Psychiatry Clinic, National Children’s Hospital, from 10/2024 – 9/2025.Results: The mean age was 7,97 ± 1,4 years. The male-to-female ratio was approximately 4,8/ 1 (82,7% boys and 17,3% girls). The most common reason for seeking medical attention was poor concentration in learning (50,9%), followed by excessive restlessness (40,9%). The common symptoms included: failure to pay close attention to details or making careless mistakes (92,7%); fidgeting with hands or feet, difficulty remaining seated (92,7%); and being easily distracted by external stimuli (91,8%). The combined presentation was the most common (74,5%), followed by the inattentive presentation (17,3%) and hyperactive-impulsive presentation (8,2%). Comorbid psychiatric disorders were present in 48,2% of cases (53/ 110), most commonly oppositional defiant disorder (35,5%), followed by anxiety disorders and sleep disorders (10%), and conduct disorder (4,5%).Conclusion: ADHD was more common in boys, with the combined presentation being the most frequent type. The most common symptoms were inattention to details and fidgeting behaviors. Associated psychiatric disorders such as oppositional defiant disorder (35,5%), conduct disorder, anxiety, and sleep disturbances.
Keywords: ADHD, neurodevelopmental disorders, children, clinical characteristics.